Mapping global research trends in swimming anatomy and physiology: A bibliometric analysis (2015-2025) - Arhesa, Sandra; Badriah, Dewi Laelatul (Journal Sport Area, 2025)
Background: Swimming performance is fundamentally influenced by the interaction between anatomical structures and physiological functions, both of which determine movement efficiency, endurance capacity, and overall athletic performance. Despite the increasing number of studies examining these aspects separately, there is still no comprehensive bibliometric investigation that systematically maps the research landscape on anatomy and physiology in swimming. Objectives: This study employs bibliometric analysis to comprehensively identify and characterize research trends within the field of anatomy and physiology as they pertain to swimming over the past decade (2015-2025). Methods: This study systematically analyzed 371 Scopus-indexed publications concerning the anatomy and physiology of swimming, published within the decade spanning 2015 to 2025. To discern prominent research trends, we employed co-word analysis and text mining techniques, facilitated by VOSviewer software. Finding/Results: The bibliometric analysis indicated an absence of a consistent upward trend in research within the field of anatomy and physiology related to swimming. Peak publication years were observed in 2015 and 2017, each recording 58 documents. Geographically, the United States was the most prolific contributor, accounting for 173 published documents. Lauder, G.V., was identified as the most influential author, having individually contributed 12 publications. Regarding subject focus, Agricultural and Biological Sciences constituted the predominant area of research, representing 193 documents (29.2%) of the total publications in this domain. Conclusion: This study provides a comprehensive overview of the evolution of research on anatomy and physiology in swimming and identifies key contributors and emerging themes for future investigation.